2005
DOI: 10.1177/107906320501700102
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Personality Characteristics of Juvenile Sex Offenders and Non-Sex Offending Delinquent Peers: A Preliminary Investigation

Abstract: There exists a paucity of research on psychopathology among Juvenile Sex Offenders (JSOs) as measured by standardized instruments, particularly as compared to nonclinical and other clinical populations. The current investigation involved a comparison of scores on the Minnesota Multiphasic Personality Inventory-Adolescent Version (MMPI-A) between a group of JSOs and non-sex offending delinquent peers. Thirty-six youth from a staff-secure residential facilitate participated, 18 JSOs and 18 non-sex offending deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 26 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Thus the JSO-H+ group in the present study showed a versatile, antisocial profile which has been often described in former studies of JSO (Butler & Seto, 2002;Freeman et al, 2005;Ronis & Borduin, 2007;Seto & Barbaree, 1997;van Wijk, Loeber et al, 2005;van Wijk, van Horn, Bullens, Bijleveld, & Doreleijers, 2005;van Wijk et al, 2006). Sexual inadequate behavior of these JSO represents a part of a more comprehensive behavioral problem which also includes general rule breaking behaviors and social deficits.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Thus the JSO-H+ group in the present study showed a versatile, antisocial profile which has been often described in former studies of JSO (Butler & Seto, 2002;Freeman et al, 2005;Ronis & Borduin, 2007;Seto & Barbaree, 1997;van Wijk, Loeber et al, 2005;van Wijk, van Horn, Bullens, Bijleveld, & Doreleijers, 2005;van Wijk et al, 2006). Sexual inadequate behavior of these JSO represents a part of a more comprehensive behavioral problem which also includes general rule breaking behaviors and social deficits.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, some studies found that JSO did not differ from violent or general juvenile offenders according to their early childhood problems, current behavioral adjustment, personality traits, antisocial attitudes and family background characteristics (Butler & Seto, 2002;Freeman et al, 2005;Ronis & Borduin, 2007;van Wijk, Loeber et al, 2005). Because of these findings, some authors concluded that JSO do not need specialized sexual treatment and may profit from intensive family and social interventions as general antisocial youth do (Letourneau et al, 2009;Ronis & Borduin, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in the field have shown data that reveal that criminal groups exert a considerable influence in the delinquent behavior of their members imposing the member's conformity to the group norms (Deslauriers et al, 2010). Recent studies reveal that refused teens from their peers are several times more riskiness to show an antisocial behavior (Freeman et al, 2005) in the same way in future compared to the non-refused children. Through interviews conducted it is aimed to explore on the risk factors that push youth to be involved in delinquent behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a study conducted, about 45% of juvenile male parents with behavior problems ( . Recent studies reveal that refused teens from their peers are several times more riskiness to show an antisocial behavior (Freeman et al, 2005) in the same way in future compared to the non-refused children. Through interviews conducted it is aimed to explore on the risk factors that push youth to be involved in delinquent behavior.…”
Section: Introductionmentioning
confidence: 99%